Synthesis and Characterization of Polystyrene Coated Functionalized γ -Fe2O3 Nanoparticles - Ali, Tayyab; Venkataraman, A (International Journal of Chemistry and Materials Research, 2014)
γ-Fe2O3 nanoparticles showing supermagnetic behaviour have been widely studied in recent years for various applications. Polymer coated functionalized γ-Fe2O3 nanoparticles have wide applications which attracted many researchers to study their different nature when they are supported with polymers. Functionalized γ-Fe2O3 nanoparticles has many applications in medical field such as MRI contrast, drug delivery, hyperthermia, magnetic gels, in cancer treatment and also used in memory devices, supermagnetic materials etc. In the present study we synthesized the polystyrene coated functionalized γ-Fe2O3 nanoparticles (PSCFNPs) in the weight ratio through grafting onto method. These nanoparticles were characterized and studied its magnetic property employing B-H loop tracer, molecular structure through FT-IR spectroscopy, thermal study employing TGA, DSC and morphology through Scanning Electron Microscopy (SEM) & transmission electron microscopy (TEM) techniques. Through the mentioned characterization techniques we obtained the formation of fine polystyrene coated functionalized γ-Fe2O3 nanoparticles. The medical applications of the nanoparticles with tailored surfaces by biocompatible polymers are envisioned.